2018
DOI: 10.1007/s10096-018-3232-8
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary percussive ventilation improves lung function in cystic fibrosis patients chronically colonized with Pseudomonas aeruginosa: a pilot cross-over study

Abstract: The trail was retrospectively registered at the ISRCTN registry on 6 June 2013, under trial registration number ISRCTN75391385.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A). However, under biofilm conditions, several biofilm marker genes, such as pelA , pslG , glpD , anr and dnr (Goodman et al , ; Son et al , ; Crabbe et al , ; ; Bielecki et al , ; Dingemans et al , ; ) as well as genes contributing to motility ( fliC, pilY1 ) were >2‐fold down‐regulated in biofilms by Δ sagS strain relative to Δ sagS::sagS (Fig. B) .…”
Section: Resultsmentioning
confidence: 97%
“…A). However, under biofilm conditions, several biofilm marker genes, such as pelA , pslG , glpD , anr and dnr (Goodman et al , ; Son et al , ; Crabbe et al , ; ; Bielecki et al , ; Dingemans et al , ; ) as well as genes contributing to motility ( fliC, pilY1 ) were >2‐fold down‐regulated in biofilms by Δ sagS strain relative to Δ sagS::sagS (Fig. B) .…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, some studies may use markers, such as sputum weight, which may be unfeasible in a pediatric population. Rigorous assessments of these methodologies may be increasingly important as new devices, including portable devices lacking clinical evidence, are proposed for patient use.…”
Section: Discussionmentioning
confidence: 99%
“…No significant changes were found over one year in either the PEP group or the OPEP group [46]. A pilot study by Dingemans et al, studied the influence of shear stress induced by IPV on the bacterial load and gene expression of P. aeruginosa in adults with CF [90]. They concluded that IPV at high frequency could potentially alter the behavior of P. aeruginosa, but this should be verified in a larger group of patients.…”
Section: Othermentioning
confidence: 99%